Investigating the relationship between types of leisure activities and coping strategies among older Korean immigrants - Jungjoo LEE; Jaehyun KIM; Donghwa HU; Jooah LEE; Junhyoung KIM (Journal of Health and Social Sciences)
Introduction: The purpose of this study was to investigate the relationship between different types of leisure activities (e.g., Leisure-Time Physical Activity (LTPA), Intellectual activity, and Community-based activity) and coping strategies (e.g., problem-solving, social support, avoidance) among older Korean immigrants. Methods: This study collected survey data from older Korean immigrants (50 to 85 years old) living in Southern Californian cities in the United States (n = 51). We conducted a hierarchical regression analysis to investigate the relationship and the change of explained variances. Results: We found that LTPA and intellectual leisure were significantly associated with the increased use of support-seeking strategies by older immigrants. Community-based leisure was positively associated with their problem-solving and avoidance strategies. Discussion: The present study not only deepens the body of knowledge describing how particular leisure activities are associated with coping strategies but also provides practical implications for helping older immigrants cope with acculturation stress and life course challenges.